Stimulation of Photoreactions of Isolated Chloroplasts by Serum Albumin - Friedlander, Michael (1968)
Serum albumin was shown to stimulate markedly various photoreactions in isolated bean and lettuce chloroplasts. The maximal effect was obtained when this compound was present during the homogenization step and continuously in the chloroplast preparation. The “basal” electron transport was enhanced using various acceptors and stimulation was obtained also in the presence of uncouplers. The quantum requirement for ferricyanide reduction was appreciably reduced. Serum albumin increased the rate of cyclic phosphorylation and the ratio of P/e(2) in non-cyclic phosphorylation. The increase in phosphorylation is supposedly due to inhibition of the rate of decay of the high energy non-phosphorylated intermediate, X(E). It is postulated that serum albumin affects chloroplast photoreactions by binding endogenously released unsaturated fatty acids.